(untitled) (Agroindustria, Sociedad y Ambiente, 2025)
In the agroindustry sector, the implementation of digital tools allows improving product traceability, optimizing the use of inputs and minimizing the environmental impact. The safeguarding of scientific information in digital form minimizes the risks of information loss and guarantees its accessibility, therefore, the objective of this research was to carry out a bibliometric analysis in conjunction with a systematic review to know the importance of digital preservation. A bibliometric analysis of 304 articles was made using the Scopus platform and, subsequently, a systematic review was carried out, extending the search to databases such as Google Scholar, latindex Scielo, Redalyc and Dialnet, to evaluate the importance, quality and relevance of digital preservation media. Among the findings, it was found that Brazil, with 153 publications, was the country with the highest scientific production, being social sciences, the Knowledge Area that contributed most to the construction of bibliographic material related to the study of preservation with 132 published documents, and the type of publication most used during the period were journal articles, representing 69% of the total scientific production, In relation to relevance and quality, it was observed that 24 selected articles highlight that digital preservation increases the visibility of Latin American scientific information, in terms of quality, it is lagging behind in comparison to developed countries when comparing bibliometric indexes. Finally, it can be mentioned that the implementation of digital preservation not only guarantees a more efficient and competitive agribusiness, but also promotes a more sustainable and inclusive development in Latin America. Therefore, it is essential to continue promoting initiatives that facilitate its adoption, closing existing gaps and ensuring that the benefits of digitization reach all levels of the agroindustry chain.